2013
DOI: 10.1177/0040517513512403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple air gaps on the thermal performance of firefighter protective clothing under low-level heat exposure

Abstract: The thermal performance of firefighters' protective clothing entrapping multiple air gaps and exposed to low heat fluxes has been studied using a newly designed bench-scale test apparatus. Different air gap sizes (0, 2 and 5 mm), and entrapped positions within the multiple fabric system between the outer shell, the moisture barrier, and the thermal liner, respectively, were investigated at three levels of thermal radiation (2, 5 and 10 kW/m2) over a prolonged period. The effect of air gap size and its position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
1
44
0
4
Order By: Relevance
“…The analogy of thermal resistance for the heat transfer with a multilayer flat wall was used to analyze the effects of air gap size and its position. However, these previous studies put emphasis on the qualitative analysis of the different air gap sizes at the dry condition .…”
Section: Introductionmentioning
confidence: 99%
“…The analogy of thermal resistance for the heat transfer with a multilayer flat wall was used to analyze the effects of air gap size and its position. However, these previous studies put emphasis on the qualitative analysis of the different air gap sizes at the dry condition .…”
Section: Introductionmentioning
confidence: 99%
“…Song ve diğerleri (2011) yapmış oldukları çalışmada katmanları içerisinde hava boşlukları bulunan kumaşlarda fazla termal enerji depolandığını ve hava boşluklu kumaş sistemlerinin termal riske maruz kalma sonrası sıkıştırıl-masının deri yanıklarını arttıracağı sonucuna ulaşmışlardır [53]. Termal koruyucu giysi giyen itfaiyeciler normal, tehlikeli ve acil durum çalışma koşullarında farklı çevre sıcaklıkları ve farklı seviyede termal ışınıma maruz kalabilmektedirler [32,41,55]. Literatürde yer alan birçok çalışmada her ne kadar tehlikeli ve acil durum çalışma koşulları için giysilerin koruma performansları araştırılmış olsa da, itfaiyeciler normal koşullar altında çalı-şırken de termal risklere maruz kalmaktadırlar [55].…”
Section: Tekstil Ve Mühendisunclassified
“…Termal koruyucu giysi giyen itfaiyeciler normal, tehlikeli ve acil durum çalışma koşullarında farklı çevre sıcaklıkları ve farklı seviyede termal ışınıma maruz kalabilmektedirler [32,41,55]. Literatürde yer alan birçok çalışmada her ne kadar tehlikeli ve acil durum çalışma koşulları için giysilerin koruma performansları araştırılmış olsa da, itfaiyeciler normal koşullar altında çalı-şırken de termal risklere maruz kalmaktadırlar [55]. İtfaiyeciler normal koşullarda çalışırken düşük seviyede termal ışınıma (5-20 kW/m 2 ) maruz kalmakta, kişilerde deri yanıkları ani yanma durumuna göre daha az olmakta ve uzun sürede oluşmaktadır [33].…”
Section: Tekstil Ve Mühendisunclassified
See 1 more Smart Citation
“…Data obtained over the years show that most burn injuries sustained by fire-fighters occurred in thermal environments with low radiation level (classified as routine or hazardous conditions), as a result of prolonged exposure [12][13][14]. So far, almost all the studies on thermal protective performance were conducted for high-level radiant heat flux corresponding to the emergency conditions; only a few studies have been conducted on thermal protective performance with prolonged exposure to hazardous conditions; and no studies have been found for the moisture influence on heat transfer through thermal protective clothing under routine conditions.…”
Section: Introductionmentioning
confidence: 99%